2018
DOI: 10.1074/jbc.m117.814509
|View full text |Cite
|
Sign up to set email alerts
|

Chondroitin sulfate–mediated N-cadherin/β-catenin signaling is associated with basal-like breast cancer cell invasion

Abstract: Tumor metastasis involves cancer cell invasion across basement membranes and interstitial tissues. The initial invasion step consists of adherence of the tumor cell to the extracellular matrix (ECM), and this binding transduces a variety of signals from the ECM to the tumor cell. Accordingly, it is critical to establish the mechanisms by which extracellular cues influence the intracellular activities that regulate tumor cell invasion. Here, we found that invasion of the basal-like breast cancer cell line BT-54… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 56 publications
(64 citation statements)
references
References 57 publications
3
61
0
Order By: Relevance
“…Notably, site-specific sulfation of CSs regulates invasion of cancer cells via the N-cadherin/β-catenin pathway. 47 Low levels of CS chains in the extracellular matrix of colorectal cancer reduce the expression of vimentin and snail family transcriptional repressor 1 (SNAI1), and increase the expression of E-cadherin. 46 Expression of the stem cell marker CD44 is increased in the mesenchymal subsets of gliomas and is closely related to EMT.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, site-specific sulfation of CSs regulates invasion of cancer cells via the N-cadherin/β-catenin pathway. 47 Low levels of CS chains in the extracellular matrix of colorectal cancer reduce the expression of vimentin and snail family transcriptional repressor 1 (SNAI1), and increase the expression of E-cadherin. 46 Expression of the stem cell marker CD44 is increased in the mesenchymal subsets of gliomas and is closely related to EMT.…”
Section: Discussionmentioning
confidence: 99%
“…Human placental pericyte glycolytic activity is inversely associated with the expression level of N-cadherin (Cantelmo et al, 2016). It has been shown that N-cadherin sequesters β-catenin to the plasma membrane, which may lower β-catenin-dependent promotion of proliferation as was shown to occur in tumor cells (Nadanaka et al, 2018). This effect may be mediated through the regulation of metabolic pathways since c-Myc, a major target gene of the β-catenin/TCF transcription factor complex, is a well-established effector of glycolysis (Li and Wang, 2008).…”
Section: Quiescencementioning
confidence: 99%
“…Overexpression of Twist and β-catenin is associated with EMT and invasiveness [92][93][94]. Actin re-organization and the formation of stress fibers are essential events for cell migration, and are considered the hallmark of EMT [95,96].…”
Section: Discussionmentioning
confidence: 99%